Overview of knowledge, attitude, gravida and education of pregnant women who suffer from emesis gravidarum by drinking ginger at Romauli Clinic 2025 - S, R. Oktaviance; Siboro, Peronika Putri; Ambarita, Bernadetta; Siallagan, Ermawaty Arisandi (Institute of Computer Science (IOCS), 2025)
In early pregnancy, nausea occurs because the hormones estrogen and progesterone increase so that there is also an increase in HCG in the blood. Research Objective: To find out how the knowledge, attitude, gravity and education of pregnant women by drinking Ginger. Research Method: This research is descriptive. The sampling technique is accidental sampling with a total of 30 respondents. Research Results: The results show that 10 pregnant women (33.3%) have good knowledge, 15 pregnant women (50%) are in the good category of knowledge, and 5 pregnant women (16.7%) were in the poor category. In the attitude, the attitude of pregnant women who are positive is 20 people (66.7%) and negative attitudes are 10 people (33.3%). In the Gravida, pregnant women in the primiGravida category are 19 people (63.3%) and the multiGravida category are 11 people (36.7%). In the education of pregnant women, 21 people (70%) are in the high school category and 9 people (30%) in the higher education category. Conclusion: Based on the results of the study, it shows that pregnant women have sufficient knowledge in overcoming Emesis Gravidarum by consuming Ginger, the majority of pregnant women's attitudes are positive, the majority of pregnant women's Gravida is primiGravida and the majority of pregnant women's education is high school. It is expected that health workers will continue to increase education about Ginger so that Emesis Gravidarum can be reduced.